Pengaruh Kesulitan Belajar terhadap Kemandirian Belajar Siswa dalam Pembelajaran Fisika - Fakhriadi Fakhriadi; Andika Kusuma Wijaya; Haris Rosdianto (Journal Innovation In Education, 2025)
The learning of physics is often considered one of the most challenging subjects for students, as it requires a deep understanding of concepts and strong analytical skills. Difficulties in comprehending the material can affect students' motivation and learning strategies, which may ultimately impact their level of learning independence. This study employs a quantitative method with a simple linear regression approach. The sample consists of 30 students from SMPN 01 Singkawang, selected using a random sampling technique. Data were collected through questionnaires measuring students' learning difficulties and learning independence. The analysis results indicate that Learning Difficulties do not have a significant effect on Learning Independence, with a p-value of 0.1531, which is greater than the significance level of 0.05. The coefficient of determination (R²) value of 0.0715 suggests that only 7.15% of the variation in Learning Independence can be explained by Learning Difficulties, while the remaining portion is influenced by other factors.